Propuesta plan especial de manejo y protección para el bien de interés cultural para la casa Streithorst sede UAN Bucaramanga (2023)
Throughout its history, Bucaramanga's architectural heritage has witnessed a process that has led to the decline of some of the city's buildings that symbolized the boom of the city's economic good times. The city has witnessed a significant development and the result of all this transformation is framed in the architectural heritage.